Upaya Kepala Daerah Dalam Percepatan Pembangunan Pendidikan di Provinsi Jambi - Sakban Sakban (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
This study aims to examine the accountability of regional heads in accelerating educational development in Jambi Province. The question in this study is why the accountability of regional heads has not been able to accelerate education development in Jambi Province. This study uses a qualitative research approach that is descriptive analytical. The data was collected by means of observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique. Data analysis techniques with data reduction, data presentation and drawing conclusions and verification. Reliability with extension techniques, participation, accuracy of observations and triangulation of data. The results of this study indicate that the efforts of regional heads to accelerate education development in Jambi Province are carried out in the form of a five-year education program or master plan, then strengthening education human resources through a number of training, upgrading, activation of professional work groups and provision of facilities and infrastructure according to existing programs. . Efforts to overcome the accountability of regional heads in accelerating education development in Jambi Province are carried out by; a) open to receiving suggestions, opinions and criticism related to education. b) improve work information systems. c) increasing the work of educators and educational personnel. Increase motivation and supervision of the work of subordinates, and e) increase the learning achievement of students.